Bronchoscopic transparenchymal nodule access: feasibility and safety in an endoscopic unit - Harzheim, Dominik; Sterman, Daniel; Shah, Pallav L.; Eberhardt, Ralf; Herth, Felix (Respiration, 2016)
Background: The minimal invasive investigation of solitary pulmonary nodules becomes increasingly important with the emergence of lung cancer screening. Objectives: We report the results of the first utilization of a recently developed procedure in a bronchoscopy suite, which approaches solitary pulmonary nodules via a transparenchymal path. Methods: This study was a prospective, single-arm interventional study. We investigated patients with a solitary pulmonary nodule detected on CT imaging, which was suspicious for malignancy. The subject's CT was employed to calculate an airway wall point of entry (POE) as well as an avascular path through lung tissue from the POE to the solitary pulmonary nodule. Using a set of catheter-based tools under fused fluoroscopy guidance, a tunnelled tract was created from the POE to the nodule. The patients were surveyed for at least 72 h in our hospital. The primary end point of the study was to evaluate the feasibility to access and biopsy solitary pulmonary nodules outside of an operation theatre. Results: Six patients were recruited, and a tunnel pathway was created in 5 patients. There were no adverse events during the procedures. Two pneumothoraces were diagnosed by chest X-ray 2 h after the procedure, with one pneumothorax requiring drainage. Adequate biopsies were obtained from all 5 patients in whom a tunnel path was created. Conclusions: This study demonstrates that bronchoscopic transparenchymal access of solitary pulmonary nodules is feasible outside an operation theatre.
Gesehen am 30.04.2020